"Just that four letter word, hope": stroke survivors' perspectives of participation in an intensive upper limb exercise program; a qualitative exploration. (2nd November 2022) - Levy, Tamina; J. Christie, Lauren; Killington, Maggie; Laver, Kate; Crotty, Maria; Lannin, Natasha A.
ABSTRACT: Background: Less than half of stroke survivors will be able to use their arm at 6 months post-stroke. Guidelines recommend the use of intensive upper limb exercise programs to optimize recovery; however, there has been limited research exploring experiences of participation in intensive programs. Aim: To identify factors influencing adherence to an intensive upper limb exercise program in people with stroke. Methods: Qualitative design. Semi-structured interviews were conducted with 20 stroke survivors who had participated in an intensive upper limb program. Perspectives of participation, including perceived barriers and enablers to program adherence were explored. Interviews were audio-recorded, transcribed, and imported into NVivo for analysis. Two authors mapped themes to the Capability, Opportunity, Motivation-Behavior (COM-B) behavior change model to identify barriers and enablers to adherence. Results: Enablers influencing adherence included: 1) routine practice times (Motivation – automatic); 2) accountability to staff (Motivation – reflective); and 3) social support (Opportunity – social). Barriers to adherence included: 1) exercises being too difficult (Capability - physical); 2) reliance on others to help (Capability - physical); and 3) difficulty 'fitting it in' (Motivation – reflective). Conclusion: Findings will inform recommendations for the delivery of intensive upper limb exercise programs to improve adherence and assist services to provide rehabilitation in a manner that enables self-directed practice by stroke survivors.